KONDISI TERUMBU KARANG PULAU KASIAK PARIAMAN PROPINSI SUMATRA BARAT PASCA GEMPA BUMI PADANG 30 SEPTEMBER 2009 - Thamrin, Thamrin; Siregar, Yusni Ikhwan; Zulkarnaini, Zulkarnaini; Delpopi, M. (Fakultas Perikanan dan Kelautan Universitas Riau, 2013)
Survey of coral reefs ecosystem was conducted around Kasiak Island waters,about 3 mill in front of Pariaman City, West Sumatera Province in July 2011. The aimof this study is to find out the effect of earthquake in 30 September 2009 to the condi-tion of coral reefs in Kasiak Island, which was occurred in the waters around 5 km infront of Padang City. The earthquake had affected in the big scale to the buildings inPariaman and Padang City, and caused many people was killed. However, from theresults to the coral reef kondision araoun Kasiak Island showed that no effect of theearthquake to the coral reef ecosystem. Then, condition of coral reefs is very good in 3m dept of the island, however their condition is very different with the deeper waters(7 m dept).